Methods to Assess How Corporate Social Responsibility Affects Organizational Performance: a Nigerian Perspective On Firms' Profitability - Sulaiman, T.H; Abalaka, J.N; Ajiteru, S.AR (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study investigates the relationship between corporate social responsibility (CSR) and the profitability of businesses in Nigeria, using secondary data from the annual reports and financial statements of ten (10) randomly selected companies over the period from 2019 to 2024. The study aims to explore how CSR practices impact the financial performance of companies, specifically examining the Profit After Tax (PAT) as a measure of profitability. Ordinary Least Squares (OLS) regression analysis is employed to analyze the data and establish the connection between CSR activities and company performance.The findings of the study show that the companies in the sample allocated less than 10% of their annual profits to CSR initiatives. This suggests that while some companies engage in CSR, their contribution remains relatively small in proportion to their overall profitability. The coefficient of determination reveals that changes in CSR activities have a significant impact on the variations observed in the performance of these companies, particularly in terms of PAT. Furthermore, the study highlights the need for stronger regulatory frameworks to enforce CSR practices. It recommends that the Nigerian government introduce laws and regulations that require firms to allocate a portion of their profits to social responsibility, ensure transparency in social accounting, and address social costs effectively. The study emphasizes that by improving CSR engagement, businesses can contribute to national development while enhancing their long-term financial performance.